Could we address the interplay between CD133, Wnt/β-Catenin, and TERT signaling pathways as a potential target for Glioblastoma therapy? - Behrooz, Amir Barzegar; Amir Hamzah, Amir Syahir (Frontiers Media, 2021)
Glioblastoma multiforme (GBM) is one of the most lethal forms of primary brain tumors. Glioblastoma stem cells (GSCs) play an undeniable role in tumor development by activating multiple signaling pathways such as Wnt/β-catenin and PI3K/AKT/mTOR that facilitate brain tumor formation. CD133, a transmembrane glycoprotein, has been used to classify cancer stem cells (CSCs) in GBM. The therapeutic value of CD133 is a biomarker of the CSC in multiple cancers. It also leads to growth and recurrence of the tumor. More recent findings have confirmed the association of telomerase/TERT with Wnt/β-catenin and the PI3K/AKT/mTOR signaling pathways. Advance studies have shown that crosstalk between CD133, Wnt/β-catenin, and telomerase/TERT can facilitate GBM stemness and lead to therapeutic resistance. Mechanistic insight into signaling mechanisms downstream of surface biomarkers has been revolutionized by facilitating targeting of tumor-specific molecular deregulation. This review also addresses the importance of interplay between CD133, Wnt/β-catenin and TERT signaling pathways in GSCs and outlines the future therapeutic goals for glioblastoma treatment.